A Pediatric Case of Pigeon Breeder's Disease in Nova Scotia - Ellen Tsai; Dominique Couture; Daniel M Hughes (Canadian Respiratory Journal)
Pigeon breeder's disease has been reported sporadically in the pediatric population since it was first described in children in 1967. Because of its infrequent occurrence in children, a high level of suspicion is often required before a diagnosis is made. A case of pigeon breeder's disease in a child in Nova Scotia, where the disease is virtually unseen or at least unrecognized, is described. The need for prompt recognition of the condition is paramount because its complications may be irreversible.